PENGARUH KREATIVITAS GURU PAI TERHADAP PRESTASI BELAJAR SISWA DI SMP NEGERI 55 KABUPATEN MERANGIN PROVINSI JAMBI - Irsyad Saifullah, Muhammad; Bahriani Putri, Dina; izzatuzzahroh; Junia Putri, Ismarani; Febriyanti; Aini, Kurratul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the lack of attention to a key aspect of achieving educational goals—namely, the psychomotor aspect—in student academic achievement at SMP Negeri 55 in Merangin Regency, Jambi Province. The objectives of this study are: 1) To determine the creativity of Islamic Education (PAI) teachers at SMPN 55 in Merangin Regency, Jambi Province; and 2) To determine the influence of PAI teachers’ creativity on student academic achievement at SMPN 55 in Merangin Regency, Jambi Province. This study employs a descriptive quantitative research method. The population of this study consists of students at State Junior High School 55 in Merangin. The sample comprises 31 respondents selected using purposive sampling. The research instrument consists of a Likert scale questionnaire. Data collection techniques include questionnaires and documentation. The data analysis technique used is simple linear regression. The results of the simple linear regression test indicate that there is a significant and positive relationship between the creativity of Islamic Religious Education teachers and student academic achievement. The results show that 68% of the 31 student respondents rated the creativity of their Islamic Religious Education teachers as “good.” Meanwhile, 45% of the 31 student respondents indicated that their academic achievement fell into the good category. Furthermore, t-calculated = (2.490) when compared to t-table, so t-calculated (2.490) > t-table (1.699), meaning that the influence of the Islamic Religious Education teacher’s creativity variable on students’ academic achievement is significant and has a positive effect.